2012
DOI: 10.1055/s-0032-1307460
|View full text |Cite
|
Sign up to set email alerts
|

Chondromyxoid Fibroma of the Anterior Skull Base Invading the Orbit in a Pediatric Patient: Case Report and Review of the Literature

Abstract: Chondromyxoid fibroma (CMF) is a rare bone tumor of cartilaginous derivation representing less than 1% of all benign bone neoplasms. It is a slow-growing, locally destructive tumor that usually affects the metaphyseal region of long bones of patients in their second or third decade of life. Involvement of the skull base and orbit is extremely rare. We present the first case of histopathology-proven CMF originating in the greater sphenoid wing and extending into the orbit in a 14-year-old boy. He complained of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
(101 reference statements)
0
8
0
Order By: Relevance
“…Chondrosarcoma, chondroblastic osteosarcoma, fibrous dysplasia, chondroblastoma, and chordoma are included in the differential diagnosis. 20 21 This is an important distinction to make given the relatively benign nature of CMF. Low-grade chondrosarcomas and CMF share stellate cells, S-100 protein stain positivity, and negative keratin stain.…”
Section: Discussionmentioning
confidence: 99%
“…Chondrosarcoma, chondroblastic osteosarcoma, fibrous dysplasia, chondroblastoma, and chordoma are included in the differential diagnosis. 20 21 This is an important distinction to make given the relatively benign nature of CMF. Low-grade chondrosarcomas and CMF share stellate cells, S-100 protein stain positivity, and negative keratin stain.…”
Section: Discussionmentioning
confidence: 99%
“…Previous cases with secondary involvement of the orbit have been described [6, 8]. As mentioned in the introduction, only 4 previous publications describe CMF with origin in the orbit, of which one had no other symptoms than headache.…”
Section: Discussionmentioning
confidence: 99%
“…Most authors recommend curettage in the skull base and facial bones, as it reduces the need for reconstruction after extensive removal of bone and the cosmetic result is therefore better. The downside is that curettage seems to increase the rate of recurrence by as much as 25%, and because of this surgical treatment should be planned with regards to the possibility of recurrence [8, 9].…”
Section: Discussionmentioning
confidence: 99%
“…Even after curettage or resection, the overall recurrence rates range from 5% to 26% (Karkuzhali et al, 2005). In our review of the literature, we found one recurrence out of 10 pediatric craniofacial CMFs (Wu et al, 1998; Crocker et al, 2010; Khalatbari et al, 2012). However, the evidence is mixed regarding the efficacy of curettage versus resection (Macan et al, 2003; Vernon and Casiano, 2006).…”
mentioning
confidence: 88%
“…In fact, a study of 278 cases of CMFs throughout the body showed only a 5.4% distribution in the skull and facial bones compared with 46.9% in long bones, 30.3% in flat bones, and 17.3% in hand and foot bones (Wu et al, 1998). To our knowledge, only 66 cases of craniofacial CMFs have been reported in the English literature (Khalatbari et al, 2012). Of these 66 craniofacial CMFs, 16 cases have mandibular involvement (Hammad et al, 1998; Macan et al, 2003).…”
mentioning
confidence: 99%